2013
DOI: 10.1007/s00592-013-0487-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence that obese patients with obstructive sleep apnea/hypopnea syndrome are refractory to the acute beneficial metabolic effects of a very low calorie diet

Abstract: Since obesity seems to play a causal role in both obstructive sleep apnea/hypopnea syndrome (OSAHS) and type 2 diabetes, the question arises whether diet-induced weight loss is equally efficacious in type 2 diabetic patients with and without OSAHS. The present study was aimed to investigate the effect of 1 week very low calorie diet (VLCD) on oxygen desaturation index (ODI) and on glucose regulation in OSAHS versus non-OSAHS patients. Fourteen patients with type 2 diabetes mellitus and morbid obesity were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…OSAHS patients with MS presented higher levels of glucose than patients without MS, but the association between aldosterone and glucose levels failed to reach statistical significance. Experimental and clinical evidence support a pathophysiologic link between OSAHS, beta cell function and glucose metabolism [3],[38]. Moreover, several cross-sectional studies have reported direct correlations between aldosterone and insulin resistance [27],[30].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…OSAHS patients with MS presented higher levels of glucose than patients without MS, but the association between aldosterone and glucose levels failed to reach statistical significance. Experimental and clinical evidence support a pathophysiologic link between OSAHS, beta cell function and glucose metabolism [3],[38]. Moreover, several cross-sectional studies have reported direct correlations between aldosterone and insulin resistance [27],[30].…”
Section: Discussionmentioning
confidence: 97%
“…Elevated aldosterone levels have been pointed to lead not only to sodium retention and volume expansion, but also to increased inflammation and oxidative stress, which in turn promote insulin resistance, impaired pancreatic β cell function, endothelial dysfunction and hypertension [35],[36]. There is also evidence that aldosterone may worsen preexisting alterations in glucose and lipid metabolism [37],[38]. In addition, a recent study demonstrated that in patients with hypertension, plasma aldosterone levels were higher in the group with MS in spite of no differences in plasma renin activity between the groups with or without MS [10].…”
Section: Discussionmentioning
confidence: 99%
“…The very low-calorie diet (VLCD) contains between 400 to 800 kcal/day and is indicated for individuals with a BMI >40 kg/m 2 who need to control their comorbidities 9,10. Its impact on the change in body composition in morbidly obese 11 and its benefits during the perioperative period of bariatric surgery have been shown in several studies 3,6,12,13. At our institution, patients with BMI>50 kg/m 2 had a weight loss approximately of 10% in 7.7 weeks with a VLCD 14.…”
Section: Introductionmentioning
confidence: 99%
“…OSAHS has severe effects on cognitive function, growth and development, and behavior of children (3). In addition, life quality also significantly decreases (4).…”
Section: Introductionmentioning
confidence: 99%